2019
DOI: 10.1159/000504838
|View full text |Cite
|
Sign up to set email alerts
|

Usability of a Wrist-Worn Smartwatch in a Direct-to-Participant Randomized Pragmatic Clinical Trial

Abstract: <b><i>Background:</i></b> The availability of a wide range of innovative wearable sensor technologies today allows for the ability to capture and collect potentially important health-related data in ways not previously possible. These sensors can be adopted in digitalized clinical trials, i.e., clinical trials conducted outside the clinic to capture data about study participants in their day-to-day life. However, having participants activate, charge, and wear the digital sensors for lon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 16 publications
1
17
0
Order By: Relevance
“…This presents a limitation to this study but also adds important information to critical care rehabilitation literature, and future studies might need to include a similar dropout rate when using smartwatches in a similar cohort or assessing a smartwatch intervention. Our smartwatch usage rates are broadly similar to those of previous studies [ 35 , 36 ], though there were no identified studies with a similar cohort that allowed for direct comparisons of use.…”
Section: Discussionsupporting
confidence: 77%
“…This presents a limitation to this study but also adds important information to critical care rehabilitation literature, and future studies might need to include a similar dropout rate when using smartwatches in a similar cohort or assessing a smartwatch intervention. Our smartwatch usage rates are broadly similar to those of previous studies [ 35 , 36 ], though there were no identified studies with a similar cohort that allowed for direct comparisons of use.…”
Section: Discussionsupporting
confidence: 77%
“…In addition, most reported monitoring systems require active participation of the users and restrict their physical independence. Another concern about the wearable systems evolves from their ease-of-use [68], [126] particularly among the older population who reportedly showed a tendency of not even activating their wrist-based fitness devices [126].…”
Section: B Non-integrated Wearable Systemsmentioning
confidence: 99%
“…Therefore, a wearable system must be user-friendly in terms of initial setup, connectivity and operational procedures. Also, an easier initial set-up process can encourage the users to continue using the devices [68], [126]. Nevertheless, all these promising research works on portable and affordable monitoring tools can potentially pave the way towards realizing a compact and wearable health monitoring system.…”
Section: B Non-integrated Wearable Systemsmentioning
confidence: 99%
“…The inherent constraints of their placement, moreover, provide a substantive benefit by reducing the number of “edge cases” that invariably arise when building intelligent sensing systems. Yet, perhaps smart speakers’ biggest advantage over mobile phones and other wearable devices is their ability to foster compliance [ 2 , 3 ] by not requiring patients to wear or do anything after initial setup (ie, they can be truly “set and forget”).…”
Section: What Are Smart Speakers and How Are They Different From Smar...mentioning
confidence: 99%